La semántica en los motores de búsqueda - Ordoñez Salinas, Sonia (Ingeniería, 2005)
This document presents a revision of the main contributions made about handling of semantics in the Search Motors or in the Systems of Information Recovery. As any other software system, the Systems of Information Recovery have architecture and some structures that allow them to work. This paper revises the general aspects of these systems, and details the treatment that has been given to the semantics inside this software. This work is framed into the computational semantics and in a general way, it presents the most relevant characteristics, in order to understand the topics treated throughout this revision.